Pengembangan UMKM di Desa Jatibaru - Dasman, Sunita; Sulistyorini Wulandari, Dian; Teguh Nugroho, Arief (DPPM Universitas Pelita Bangsa, 2023)
Micro, small and medium enterprises (MSMEs) are productive economic enterprises that stand alone and are carried out by individuals or business entities that are capable of expanding employment and providing broad economic services to the community. Jatibaru Village is a village with the majority of the population being traders, farmers and MSME actors whose family's source of income is economically derived from selling and farming activities. During the Covid-19 pandemic, MSMEs experienced a significant decrease in turnover. The lack of knowledge, especially in the field of the digital world, is still lacking, they rely more on regular customers who are limited and uncertain. In addition, there is a lack of creativity in utilizing digital tools for online social media which are moving rapidly.